Ethnopharmacological Perspective for Treatment of Epilepsy: An Updated Review - Sunishtha Kalra; Saurabh Bhatia; Ahmed Al Harrasi; Syam Mohan; Himanshu Sachdeva; Divya Sharma; Vikas Budhwar; Manjusha Choudhary; Rohit Malik (Scientifica)
Plants have been used as healing agents since humanity began. This review presents the plant profiles inhabiting the world regarding their traditional usage by various tribes/ethnic groups for the treatment of epilepsy. The bibliographic investigation was carried out by analyzing standard reference textbooks, Science Direct, Google Scholar, Scopus, Medline, Web of Science, and PubMed databases. Search terms and keywords used for the search were epilepsy, medicinal plants for epilepsy, herbal remedies used in the treatment of epilepsy, and traditional antiepilepsy medication. This review article was prepared by including the biological names of plants/their parts/extracts/compounds/doses/models/results. Further, experimentally explored 15 potential medicinal plants have also been explored in detail. The present review was prepared by including 114 plants from 3 books, 83 research, and 59 review articles. This review indicates that the list of medicinal plants presented in this review might be useful to researchers for preliminary screening of potential antiepileptic agents.